1997
DOI: 10.1111/j.1550-7408.1997.tb05702.x
|View full text |Cite
|
Sign up to set email alerts
|

Small Subunit Ribosomal RNA Sequences Unite Alternate Actinosporean and Myxosporean Stages of Myxobolus cerebralis the Causative Agent of Whirling Disease in Salmonid Fish

Abstract: The alternating myxosporean and actinosporean stages of the myxozoan parasite Myxobolus cerebralis (Hofer 1903) from its salmonid fish and aquatic oligochaete hosts, respectively, were compared for sequence homology of the small subunit (18s) ribosomal RNA genes. A 99.8% similarity between the sequences of these two stages was substantially greater than that of M . cerebralis compared to two other Myxobolus sp. from salmonid fish. Our results are the first molecular evidence confirming the alternating stages i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 23 publications
(8 reference statements)
1
39
0
1
Order By: Relevance
“…(1989). The 18s rDNA sequencing and alignments of sequences were performed as described previously (Andree et al 1997). The 1700 bp fragment of the 18s rDNA from Myxobolus neurobius, M. insidiosus, M. arcticus, and M. squamalis was amplified using primers MX5 and MX3.…”
Section: Sources Of Spores Spores Of Myxobolus Cerebralismentioning
confidence: 99%
See 2 more Smart Citations
“…(1989). The 18s rDNA sequencing and alignments of sequences were performed as described previously (Andree et al 1997). The 1700 bp fragment of the 18s rDNA from Myxobolus neurobius, M. insidiosus, M. arcticus, and M. squamalis was amplified using primers MX5 and MX3.…”
Section: Sources Of Spores Spores Of Myxobolus Cerebralismentioning
confidence: 99%
“…DNA extractions, sequencing, and alignments of rDNA. DNA extractions were carried out as described for myxosporeans (Andree 1997). DNA isolation from whole tissue and from transformant bacterial cells was performed as described by Sambrook et al.…”
Section: Sources Of Spores Spores Of Myxobolus Cerebralismentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no generally accepted baseline of genetic distance that allow the distinction between species boundaries, several studies have indicated that the divergence is well within the value (<2%) determined for same species isolates from different hosts or geographic locations (Hallett et al 2004;Whipps and Kent 2006;Yokoyama et al 2006;Urawa et al 2009). An interspecific pairwise comparison for 1,700 bp of 18S rDNA sequences from ten Myxobolus species indicated a 71.9-97.7% similarity (Andree et al 1997). This novel type spore does not correspond to any of the triactinomyxon already sequenced, and the closest relatives found were the Triactinomyxon types identified by Hallett et al (2005), with low similarity (80.33%) in their 18S rDNA sequences, suggesting it is a novel type.…”
Section: Discussionmentioning
confidence: 99%
“…These methods will be employed not only for the diagnostic purposes, but also in the studies of life-cycles of myxosporeans. Andree et al (1997), Bartholomew et al (1997) and Anderson et al (2000) successfully performed the 18SrDNA analysis, and united alternate actinosporean and myxosporean stages on the molecular basis.…”
Section: Discussionmentioning
confidence: 99%